PENGGUNAAN MEDIA VIDEO PADA MATERI MENGHAFAL DI RA BANI MALIK LEDUG - Mardiyah, Naini; Yahya, Slamet (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to find out how the use of video media in conveying memorization material, especially in al-Islam lessons at RA Bani Malik Ledug. The method used is a qualitative method through a descriptive approach. Research data obtained through interviews and observations and then analyzed with qualitative analysis techniques. The results showed that through video media the memorization process became easier because the teacher could do demonstrations. Where the teacher can carry out the process of recording the memorization movement method which can be videoed or uploaded via YouTube. It is very possible that this makes young children become enthusiastic in practicing by watching the videos that are served when learning al-Islam material which emphasizes memorization material. Early childhood basically has physical, emotional, intelligence and religious moral development, so that when we invite them to move by watching videos it can easily enter their brains. The video media has advantages such as: 1) students are excited when listening to murattal so that students are able to focus on the material being memorized. 2) the use of this video media can be played repeatedly. 3) through the movements in the video, of course, it can improve students' memory which is stored in long term memory. 4) students can learn independently. While the shortcomings of this video media are the differences in the character of students, where there are children who focus on paying attention and some focus on playing. Because early childhood learning activities are pursued by the world of play, so teachers must be patient and inappropriate to use authoritarian nature in conveying their learning activities.